Tanggung Jawab Notaris Menggunakan Layanan Ditjen Ahu Online Dalam Hal Pendaftaran Akta Dan Pengesahan Badan Hukum - Suryawan, I Gede Agus Yudi; Asmara Putra, Dewa Nyoman Rai (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
In accordance with the Decree of the Minister of Justice and Human Rights Number M-05 HT.01.01 of 2002 concerning the Enforcement of the Legal Entity Administration System at the Directorate General of General Legal Administration of the Ministry of Justice and Human Rights of the Republic of Indonesia, determines that all legal entity settlements include the ratification of the deed of establishment PT, application for approval and submission of deed reports, amendments to articles of association, fiduciary registration, will registration, are carried out with the online Legal Entity Administration System. So the notary has the authority to register all these legal acts online. The purpose of this research is to find out the role of the Notary in registering deeds and legalization of legal entities through the Directorate General of AHU Online services and to find out the responsibilities of the Notary if there are problems in registering deeds and legal entity approval through the services of the Directorate General of AHU Online. This study uses a normative juridical research method using a statutory approach and a conceptual approach. The results of the research, namely, the role of the notary in registering deeds and ratifying legal entities is entering deed data, checking all deed data to avoid data entry errors and the notary has the responsibility if there is an error from the notary's office, the notary will make corrections at a cost of Notary, however in this regard there is still cooperation from the applicant regarding the required data.